FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEBIASAAN KONSUMSI TABLET TAMBAH DARAH SEBAGAI UPAYA PENCEGAHAN ANEMIA PADA REMAJA PUTERI (STUDI PADA MAHASISWA TAHUN PERTAMA DI FAKULTAS KESEHATAN MASYARATAK UNIVERSITAS DIPONEGORO) - Temi Chintia Risva; Suyatno Suyatno; M. Zen Rahfiludin (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Anemia iron deficiency is a common morbidity among adolescents due to their high need of nutrition for their growth. Iron supplementation is the solution for this problem. This study aims to find factors that are associated to iron tablet consumption behavior on female adolescents in Faculty of Public Health Diponegoro University. This is a quantitative study that use cross sectional design. Samples of this study were calculated using case control calculation with Lameshow formula. Data were collected using questionnaire and analyzed using chi-square with Odds ratio value calculation. The unvaried calculation finds that among case and control group, there are 43.5% and 45.2% respondents with good knowledge, 41.9% and 61.3% with good awareness, 59.7% and 48.5% with good purchasing power, 54.7% and 79.0% with good supply, 41.9% and 54.5% with good surrounding behavior, and also 50.0% and 75.8% with good support from surrounding. The study finds that factors associated with iron tablet consumption behavior on female adolescents in Faculty of Public Health Diponegoro University are awareness (OR= 2.192; CI95%= 1.069-4.495), support from surrounding (OR= 2.517; CI95%= 1.220-5.196), and supports from surrounding (OR= 3.133; CI95%= 1.458-6.735). These mean that respondents with good awareness, surrounding behavior, and surrounding support, are more likely to consume iron tablet 2.1 times, 2.5 times, and 3.1 time than respondents with bad awareness, surrounding behavior, and surrounding support. Based on the result of this study, writer suggest that effort to socialize information of anemia and way to prevent it should be widen not only to female adolescent but also to their family and people surround them.